Sokolsky Grigory Ivanovich: contribution to the development of domestic and world medicine. To the 215th anniversary of the birth - D. I. Abdulganieva; G. I. Nurullina; T. N. Khalfina; D. A. Ismagilova; N. A. Trusov (Кардиоваскулярная терапия и профилактика)
The article is dedicated to the 215th anniversary of the birth of Grigory Ivanovich Sokolsky, a well-known Russian clinician and scientist who made a huge contribution to the development of clinical diagnostics of diseases, phthisiology, internal diseases, especially rheumatology. The work that laid the foundation for the scientific activity of G.I. Sokolsky, "On the rheumatism of the cardiac muscle tissue" (1836), brought him national and world fame, and formed the theory that rheumatism is a systemic disease with a primary lesion of the heart and joints. G.I. Sokolsky sought to teach students at the bedside. He was the first who began to demonstrate patients in lectures and actively introduce auscultation and percussion into clinical practice, as well as into teaching, paying special attention to their exceptional diagnostic significance and the need for joint use. An outstanding mind, broad erudition, passion, deep faith in his ideas caused an ambiguous attitude of contemporaries, which left its mark on life. The article presents previously unpublished facts about the life of G.I. Sokolsky, his activities and personality traits, unique archival documents, photographs and manuscripts.